2017
DOI: 10.13189/ujer.2017.050314
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Using Jigsaw Method Based on Cooperative Learning Model in the Undergraduate Science Laboratory Practices

Abstract: The main aim of the present study is to determine the influence of a Jigsaw method based on cooperative learning and a confirmatory laboratory method on prospective science teachers' achievements of physics in science teaching laboratory practice courses. The sample of this study consisted of 33 female and 15 male third-grade prospective science teachers (6th term) who attended science teaching laboratory practices course in the 2014-2015 academic year. In the research, science teaching laboratory practices co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 32 publications
5
48
0
5
Order By: Relevance
“…Studies reporting a significant effect were Baydar and Şimşek (2018); Karaçöp (2017); Doymuş (2008); Gündoğdu, Ozan, Taşgın (2013); Artut and Tarim (2007); Şimşek, Doymuş, Doğan and Karaçöp (2009). Both Baydar and Şimşek (2018) conducting their study in the context of teaching principles and methods compared Jigsaw I to another method; and Karaçöp (2017) in the context of science laboratory practice; Doymuş (2008) in a context of chemical bonding; Gündoğdu, Ozan and Taşgın (2013) in the context of educational psychology course and Şimşek, Doymuş, Doğan and Karaçöp (2009) conducting their studies comparing Jigsaw to conventional methods, all reported a significant effect on academic achievement of pre-service primary-elementary teachers. Only Artut and Tarim (2007) in their study, different from the rest, implemented Jigsaw II in the context of maths teaching, also reporting a significant effect of Jigsaw on academic achievement (n = 6) as in Table 5.…”
Section: Jigsaw As a CL Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reporting a significant effect were Baydar and Şimşek (2018); Karaçöp (2017); Doymuş (2008); Gündoğdu, Ozan, Taşgın (2013); Artut and Tarim (2007); Şimşek, Doymuş, Doğan and Karaçöp (2009). Both Baydar and Şimşek (2018) conducting their study in the context of teaching principles and methods compared Jigsaw I to another method; and Karaçöp (2017) in the context of science laboratory practice; Doymuş (2008) in a context of chemical bonding; Gündoğdu, Ozan and Taşgın (2013) in the context of educational psychology course and Şimşek, Doymuş, Doğan and Karaçöp (2009) conducting their studies comparing Jigsaw to conventional methods, all reported a significant effect on academic achievement of pre-service primary-elementary teachers. Only Artut and Tarim (2007) in their study, different from the rest, implemented Jigsaw II in the context of maths teaching, also reporting a significant effect of Jigsaw on academic achievement (n = 6) as in Table 5.…”
Section: Jigsaw As a CL Methodsmentioning
confidence: 99%
“…As for the contexts, the studies comparing CL to conventional methods were majorly used in science teaching departments: Karaçöp (2016) in electrochemical cells; Alyar and Doymuş (2015) in the particulate nature of matter; Şimşek, Doymuş, Doğan and Karaçöp (2009) in teaching of chemical equilibrium unit; Demirbaş, Bozdoğan and Taşdemir (2008) in the unit of electricity, also as a sub-theme (emerging in Jigsaw theme) Karaçöp (2017) in science teaching laboratory courses; Doymuş (2008) in teaching chemical bonding. The rest of the studies comparing CL to traditional methods were used in different contexts other than science were as follow: Karababa (2009) in teaching Turkish syntax; Gündoğdu, Ozan and Taşgın (2013) in educational psychology course; Artut and Tarim (2007) in maths teaching course.…”
Section: Comparison Of CL With Traditional Methods (Tms)mentioning
confidence: 99%
“…There is evidence that jigsaw can result in positive outcomes, with student performance being similar or in many cases improved when compared to traditional instruction. This outcome has been demonstrated for a variety of sciencerelated content (Slish, 2005;Depaz and Moni, 2008;Doymus, 2008a,b;Jansoon et al, 2008;Tarhan and Sesen, 2012;Karacop and Doymus, 2013;Tarhan et al, 2013;Salomaki et al, 2014;Walker et al 2015;Karacop, 2017;Sagsoz et al, 2017). In first year chemistry, jigsaw has consistently been shown to be an effective method of teaching with students achieving higher test scores and greater understanding of concepts (Doymus et al, 2010;Tarhan and Sesen, 2012;Karacop and Doymus, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…These studies mostly focused on the students’ attitudes about themselves, school, peers, academic abilities and self‐esteem. The jigsaw method, or more broadly CL, has recently experienced more widespread adoption in both high school and tertiary levels (Carrol, ; Perkins and Saris, ; Doymus, ; Jansoon et al, ; Doymus et al, ; Karacop and Doymus, ; Warfa, ; Apugliese and Lewis, ; Karacop, ). Studies in health and medicine education include undergraduate teaching of biology (Slish, ), pharmacology (Depaz and Moni, ), physiology (Bhandari et al, ), veterinary anatomy dissection (Salomaki et al, ), dentistry (Sagsoz et al, ) and medicine (Buhr et al, ; Walker et al ; Kumar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The original meaning of the group cooperative learning is not only to learn knowledge, but more importantly, to enable students to analyze, summarize, deduct and other thinking methods in the process of discussion and learning, to improve students' ability to use the knowledge they have learned to analyze and solve problems. Through long-term investigation and research, it is found that the group cooperative learning mode can fully mobilize the students' enthusiasm for learning and the ability to unite and cooperate [2]. It has its own unique advantages compared with traditional teaching, as follows:…”
Section: The Advantages Of Group Cooperative Learningmentioning
confidence: 99%